2010
DOI: 10.1007/s00430-010-0169-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inhibitors of arachidonic acid metabolism on prostaglandin E2 production by Candida albicans and Candida dubliniensis biofilms

Abstract: Arachidonic acid (AA) is released from infected host cells during Candida albicans infection and may serve as carbon source for yeast growth and as precursor for the production of biologically active eicosanoids, such as prostaglandin E₂ (PGE₂) by C. albicans. However, the mechanism involved in this production is still unclear. Therefore, it was of interest to investigate the effect of different arachidonic acid metabolism inhibitors on PGE₂ production by biofilms of C. albicans and the closely related C. dubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 20 publications
(35 reference statements)
1
28
1
Order By: Relevance
“…However, they appear to be important metabolites, since we found that cyclooxygenase inhibitors prevented hyphal growth and zoospore germination of S. parasitica, even in the absence of a clear COX homologue. This apparent paradox has also been reported in true fungi, such as Candida spp., where although no COX homologue is known, COX inhibitors prevent PGE 2 production, the yeast-hypha transition, yeast and hyphae growth, and biofilm formation (23,(39)(40)(41)(42). The exact role of these lipids in oomycete biology needs to be further addressed, as off-target effects of aspirin and indomethacin cannot be ruled out at this point.…”
Section: Discussionmentioning
confidence: 99%
“…However, they appear to be important metabolites, since we found that cyclooxygenase inhibitors prevented hyphal growth and zoospore germination of S. parasitica, even in the absence of a clear COX homologue. This apparent paradox has also been reported in true fungi, such as Candida spp., where although no COX homologue is known, COX inhibitors prevent PGE 2 production, the yeast-hypha transition, yeast and hyphae growth, and biofilm formation (23,(39)(40)(41)(42). The exact role of these lipids in oomycete biology needs to be further addressed, as off-target effects of aspirin and indomethacin cannot be ruled out at this point.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence reveals that candidiasis is associated with high levels of PGE 2 (Noverr et al, 2003), and decreased prostaglandin production during C. albican infections is an important factor in relieving chronic infections (Mishra et al, 2014). In addition, research suggests that PGE 2 is produced in both C. albicans planktonic and biofilm cells (Ells et al, 2011), while biofilm cells secreted significantly more PGE 2 than the planktonic cells when determined according to cell dry weight. This may be one of the mechanisms that explain the high resistance of biofilm cells (Alem and Douglas, 2005).…”
Section: Pge2 and Candida Biofilmmentioning
confidence: 99%
“…However, our results showed that PGE2 only partly inhibited the antifungal activity of aspirin (Table 1). Recently, Ells et al (2011) showed that fungal PGE2 from C. albicans and Candida dubliniensis biofilms enhanced germ tube formation in both yeasts, and aspirin inhibited approximately 70% of fungal PGE2 production. These authors and other studies had reported the involvement of multicopper oxidase enzymes and cytochrome P450 enzymes (CYP) in the PGE2 production by C. albicans and C. dubliniensis biofilms (Erb-Downward and Noverr 2007;Erb-Downward et al 2008;Ells et al 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Ells et al (2011) showed that fungal PGE2 from C. albicans and Candida dubliniensis biofilms enhanced germ tube formation in both yeasts, and aspirin inhibited approximately 70% of fungal PGE2 production. These authors and other studies had reported the involvement of multicopper oxidase enzymes and cytochrome P450 enzymes (CYP) in the PGE2 production by C. albicans and C. dubliniensis biofilms (Erb-Downward and Noverr 2007;Erb-Downward et al 2008;Ells et al 2011). Moreover, antifungal effects attributed to aspirin have been associated with inhibiting the formation of 3(R)-hydroxyoxylipins (Deva et al 2001) and of an extracellular fungal lipase (Trofa et al 2009).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation